Transcription activator WCC recruits deacetylase HDA3 to control transcription dynamics and bursting in Neurospora - Oehler, Michael; Geisser, Leonie; Diernfellner, Axel; Brunner, Michael (Science advances, 2023)
RNA polymerase II initiates transcription either randomly or in bursts. We examined the light-dependent transcriptional activator White Collar Complex (WCC) of Neurospora to characterize the transcriptional dynamics of the strong vivid (vvd) promoter and the weaker frequency (frq) promoter. We show that WCC is not only an activator but also represses transcription by recruiting histone deacetylase 3 (HDA3). Our data suggest that bursts of frq transcription are governed by a long-lived refractory state established and maintained by WCC and HDA3 at the core promoter, whereas transcription of vvd is determined by WCC binding dynamics at an upstream activating sequence. Thus, in addition to stochastic binding of transcription factors, transcription factor-mediated repression may also influence transcriptional bursting.
Online: 30. Juni 2023
Gesehen am 23.10.2023